Связь изменений климата с геомагнитным полем. 3. Северное и Южное полушария - Килифарска, Н.А.; Бахмутов, В.Г.; Мельник, Г.В. (Геофизический журнал, 2016)
Показано відмінності розглянутих раніше зв’язків між геомагнітним полем і кліматом для Північної і Південної півкуль. Вони пов'язані насамперед з глибиною проникнення в атмосферу Землі заряджених частинок, модульованих геомагнітним полем і їх впливом на баланс озону поблизу тропопаузи. Формування озону в нижній стратосфері відбувається у Північній півкулі в іонно-молекулярному авто каталітичному циклі його утворення, ініційованому галактичними космічними променями, у Південній — внаслідок ефекту "самовіднов-лення”, ініційованого сонячними енергійними частинками. Пояснено спостережуване одночасне потепління в Західній Антарктиці і похолодання — в Центральній і Східній. Differences of relations between geomagnetic field and climate for Northern and Southern hemispheres considered earlier have been shown. They are connected, first of all, with the depth of penetration of the charged particles into the Earth’s atmosphere, modulated by geomagnetic field and their impact on the ozone balance near the tropopause. In the Northern hemisphere ozone formation in the lower stratosphere occurs during ionic-molecular autocatalitic cycle of ozone production, initiated by GCR, and in the Southern one — as a result of “self-reduction” of ozone initiated by solar energetic particles. Explanation of the observed simultaneous warming in the Western Antarctica and the fall of temperature in the Central and Eastern Antarctica has also been presented.